SIFAT-SIFAT PAPAN PARTIKEL KAYU KELAPA - Rozak Memed; Paribotro Sutigno; I M Sulastiningsih (Jurnal Penelitian Hasil Hutan, 1984)
This report  deals with the  laboratory  tests  on  the  properties of  particle board made  from  coconut  wood  and from  coconut wood with  hardwood bonded by urea formaldehyde. The  tests include board density, moisture  content, water absorption, thickness swelling and bending  strength.The  result  reveals that physical and  mechanical  properties of  particle boards  made  from  coconut wood  conform with FAO Standard.  The  properties  of  particle boards  made  from   coconut  wood mixture  with  hardwood in  the proportion of  1 : 1 which conform the  FAO  Standard are limited to density and water absorption.